A novel model for in vivo quantification of immediate liver perfusion impairment after pancreatic islet transplantation. Issue 6 (2nd November 2019) - Kosinova, Lucie; Patikova, Alzbeta; Jirak, Daniel; Galisova, Andrea; Vojtiskova, Alzbeta; Saudek, Frantisek; Kriz, Jan
ABSTRACT: Instant Blood-Mediated Inflammatory Reaction (IBMIR) is a major cause of graft loss during pancreatic islet transplantation, leading to a low efficiency of this treatment method and significantly limiting its broader clinical use. Within the procedure, transplanted islets obstruct intrahepatic portal vein branches and consequently restrict blood supply of downstream lying liver tissue, resulting typically in ischemic necrosis. The extent of ischemic lesions is influenced by mechanical obstruction and inflammation, as well as subsequent recanalization and regeneration capacity of recipient liver tissue. Monitoring of immediate liver perfusion impairment, which is directly related to the intensity of post-transplant inflammation and thrombosis (IBMIR), is essential for improving therapeutic and preventive strategies to improve overall islet graft survival. In this study, we present a new experimental model enabling direct quantification of liver perfusion impairment after pancreatic islet transplantation using ligation of hepatic arteries followed by contrast-enhanced magnetic resonance imaging (MRI). The ligation of hepatic arteries prevents the contrast agent from circumventing the portal vein obstruction and enables to discriminate between well-perfused and non-perfused liver tissue. Here we demonstrate that the extent of liver ischemia reliably reflects the number of transplanted islets. This model represents a useful tool for in vivo monitoring of biological effect of IBMIR-alleviating interventions as well as other experiments related to liver ischemia. This technical paper introduces a novel technique and its first application in experimental animals.